Nutritional status and weight gain in pregnant women Estado nutricional y aumento de peso en la mujer embarazada Estado nutricional e ganho de peso de gestantes - Ana Paula Sayuri Sato; Elizabeth Fujimori (Universidade de São Paulo, 2012)
This study described the nutritional status of 228 pregnant women and the influence of this on birth weight. This is a retrospective study, developed in a health center in the municipality of São Paulo, with data obtained from medical records. Linear regression analysis was carried out. An association was verified between the initial and final nutritional status (p<0.001). The mean of total weight gain in the pregnant women who began the pregnancy underweight was higher compared those who started overweight/obese (p=0.005). Weight gain was insufficient for 43.4% of the pregnant women with adequate initial weight and for 36.4% of all the pregnant women studied. However, 37.1% of those who began the pregnancy overweight/obese finished with excessive weight gain, a condition that ultimately affected almost a quarter of the pregnant women. Anemia and low birth weight were uncommon, however, in the linear regression analysis, birth weight was associated with weight gain (p<0.05). The study highlights the importance of nutritional care before and during pregnancy to promote maternal-infant health. Estado nutricional de 228 embarazadas y su influencia en el peso al nacer fue caracterizado. Estudio desarrollado en centro de salud de São Paulo con datos obtenidos de registros médicos. Análisis de regresión lineal fue realizado. Se verificó asociación entre estado nutricional inicial y final (p<0,001). La media del aumento total de peso disminuyó de las mujeres que iniciaran el embarazo con bajo peso para las que comenzaron con sobrepeso/obesidad (p=0,005), siendo insuficiente para 43,4% y 36,4% de embarazadas con peso adecuado inicial y para el total, respectivamente. Sin embargo, 37,1% de las que comenzaron el embarazo con sobrepeso/obesidad finalizó con ganancia excesiva, condición que afectó casi un cuarto del total. Anemia y bajo peso al nacer fueron poco frecuentes, pero peso al nacer se asoció con aumento materno de peso (p<0,05). El estudio destaca la importancia de la atención nutricional antes y durante el embarazo para promover la salud materna e infantil. Caracterizou-se estado nutricional de 228 gestantes e sua influência no peso ao nascer. Trata-se de estudo retrospectivo desenvolvido num centro de saúde do município de São Paulo, com dados obtidos de prontuários. Realizou-se análise de regressão linear. Verificou-se associação entre estado nutricional inicial e final (p<0,001). A média de ganho total de peso diminuiu das gestantes que iniciaram a gravidez com baixo peso para aquelas que iniciaram com sobrepeso/obesidade (p=0,005), sendo insuficiente para 43,4 e 36,4% das gestantes com peso inicial adequado e para o total das gestantes estudadas, respectivamente. Entretanto, 37,1% daquelas que iniciaram a gravidez com sobrepeso/obesidade finalizaram com ganho excessivo, condição que, no final, afetou quase um quarto das gestantes. Anemia e baixo peso ao nascer foram pouco frequentes, porém, na análise de regressão linear, peso ao nascer associou-se com ganho de peso (p<0,05). Evidencia-se a importância do cuidado nutricional antes e durante a gravidez, para promoção da saúde materno-infantil.